Research support for academics - Case studies of two Vietnamese Universities - Denison, Tom (Library and Information Research, 2019)
Academic in Vietnamese universities are under increasing pressure with ragard to improved research outcomes, including publications. This article reports on the findings of a research project which focused on two universities, Vietnam National University, in order to gain a rich understanding of the current state of play, the role of libraries in providing research support, and the constraints within which the various stakeholders operate. The main findings from the interviews sugest that, although researchers recognise the importance of the libraries in.